The Effectiveness of e-learning in Staff Training to Gain Hospitality Organizational Excellence - Hasan, Mahmudul (AIUB Journal of Business and Economics, 2019)
This paper discovers the state of e-learning within hospitality industry. It introduces relevant topics such as definition, employee attitude and other factors of hospitality e-learning. It critically reviews the growth of e-learning in hospitality companies. Moreover, the author identifies the development of e-learning in hospitality industry by addressing recent cases. A literature review is conducted, and the research involves survey questionnaire and semi-structured interview to collect data from users of Hilton e-learning resources and a statistical analysis of that data. Findings of the study indicate positive perceptions of e-learning among hospitality companies. However, the main finding is the identification of several concerns that can potentially prevent the users to utilize the complete advantage of e-learning. The findings should assist policy makers, instructors and e-learning implementers in designing course materials or improving technical matters that would be more effective for e-learning at hospitality environment.